PENERAPAN COSINE SIMILARITY SEBAGAI METODE PENGUKURAN SIMILARITY INDEX PADA SISTEM PENGAJUAN JUDUL SKRIPSI STKIP PGRI SUMATERA BARAT - Pernanda, Anggri Yulio; Hakiki, Muhammad (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2021)
The process of submitting a thesis will pass the validation stage by the validator team. However, as the number of titles that have been submitted increases, it will be difficult for the validator to know whether the title has been submitted before or not. We need a system that can process information retrieval against the thesis title database and is able to calculate the degree of similarity of the title. In this study, a system development was carried out by applying the Cosine Similarity method to obtain the similarity value of the proposed title to the thesis title contained in the database. The result of this research is a system that can be used as a tool for information retrieval. The information generated from this process is the degree of similarity index of the title of thesis database, which becomes a tool in conducting the title of thesis validation process in STKIP PGRI West Sumatra